In meiner eigenen Erfahrung - Koenig, Gottfried (Musica/Tecnologia, 2010)
Gottfried Michael Koenig goes over the terms of the relationship with the technology in relation to his experience, considering the fundamental steps with the objective of establishing some steady points. These considerations lead him to reaffirm the primacy of the compositional idea on the technological means, a principle which he considers even more valid today, where technology certainly can be used, but to which any moral authority cannot be delegated.